A DFNA5 Mutation Identified in Japanese Families with Autosomal Dominant Hereditary Hearing Loss. (10th February 2014) - Nishio, Ayako; Noguchi, Yoshihiro; Sato, Tatsuya; Naruse, Taeko K.; Kimura, Akinori; Takagi, Akira; Kitamura, Ken
Summary Mutations in DFNA5 lead to autosomal dominant nonsyndromic hereditary hearing loss (NSHHL). To date, four different mutations in DFNA5 have been reported to cause hearing loss. A 3 bp deletion mutation (c.991‐15_991‐13del) was identified in Chinese and Korean families with autosomal dominant NSHHL, which suggested that the 3 bp deletion mutation was derived from a single origin. In the present study, we performed genetic screening of mutations in the interval between intron 6 and exon 9 of DFNA5 in 65 Japanese patients with autosomal dominant NSHHL and identified the c.991‐15_991‐13del mutation in two patients. Furthermore, we compared the DFNA5‐linked haplotypes consisting of intragenic SNPs between the reported Chinese and Korean families and found that the Japanese patients showed a shared region spanning 41, 874 bp. This is the first report of DFNA5 mutations in Japanese patients with autosomal dominant NSHHL, supporting the suggestion that the 3 bp deletion mutation occurred in their ancestors.